Risks of children using duit Raya to buy vape - Amar, Daud Iskandar Abdullah *; Long, Chiau Ming * (Star Media Group Berhad, 2023)
Children could be using money received as "duit Raya" to buy vape and ecigarette liquids, say two doctors.